PENGARUH SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG TERHADAP PENGENDALIAN INTERN PERSEDIAAN BARANG PADA TOKO BESI DAN BANGUNAN SERBAGUNA DI AJIBARANG - Mugiarti Mugiarti; Rofi Rachmatiko; Siska Khurniyati Supraja (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
This study aimed to examine the effect of variable X, namely Accounting Information System Inventory and Y is the Internal Control Inventory of Toko Besi dan Bangunan Serba Guna at Ajibarang. Based on the research results show that the Accounting Information System Inventory (X) is categorized either by value 3.79. Internal Control Inventory (Y) is also said to be good with a value of 4.11.Effect of Accounting Information System for Internal Control Inventory based research methods, namely, 1) Correlation, based on calculations between variables X and Y has a strong relationship that is equal to 0.750, 2) Regression, based on the data through a simple regression of Y = 0.327 + 0.895X which means each an increase of Accounting Information Systems Inventory role in Internal Control Inventory amounted to 56.30%, while the remaining 43.70% due to the influence of others.At the end, the authors expressed conclusions and suggestions to the company as an input. Although the Accounting Information Systems Inventory is already done well, the system implemented should always follow the conditions that occur at any time and be a directed preparation. Also, Internal Control Inventory is already good and sufficient, therefore, it needs to be maintained and enhanced in order to generate a better and more efficient Internal Control Inventory.